Investigating a Moche Cast Copper Artifact for Its Manufacturing Technology. Issue 1656 (22nd August 2014) - Shugar, Aaron; Notis, Michael; Newbury, Dale; Ritchie, Nicholas
ABSTRACT: A Moche cast copper alloy object was investigated with focus on three main areas: the alloy composition, the casting technology, and the corrosion process. This complex artifact has thin connective arms between the body and the head, a situation that would be very difficult to cast. The entire artifact was mounted and polished allowing for complete microstructural and microchemical analysis, providing insight into the forming technology. In addition, gigapixel x-ray spectrum imaging was undertaken to explore the alloy composition and the solidification process of the entire sample. This process used four 30 mm 2 SDD-EDS detectors to collect the 150 gigabyte file mapping an area of 46 080 × 39 934 pixels. Raman analysis was performed to confirm the corrosion compounds.